Determining the spectra of radiation belt electron losses: Fitting DEMETER electron flux observations for typical and storm times. Issue 12 (9th December 2013) - Whittaker, Ian C.; Gamble, Rory J.; Rodger, Craig J.; Clilverd, Mark A.; Sauvaud, Jean‐André
<x xml:space="preserve">Abstract</x> [1] The energy spectra of energetic electron precipitation from the radiation belts are studied in order to improve our understanding of the influence of radiation belt processes. The Detection of Electromagnetic Emissions Transmitted from Earthquake Regions (DEMETER) microsatellite electron flux instrument is comparatively unusual in that it has very high energy resolution (128 channels with 17.9 keV widths in normal survey mode), which lends itself to this type of spectral analysis. Here electron spectra from DEMETER have been analyzed from all six years of its operation, and three fit types (power law, exponential, and kappa‐type) have been applied to the precipitating flux observations. We show that the power law fit consistently provides the best representation of the flux and that the kappa‐type is rarely valid. We also provide estimated uncertainties in the flux for this instrument as a function of energy. Average power law gradients for nontrapped particles have been determined for geomagnetically nondisturbed periods to get a typical global behavior of the spectra in the inner radiation belt, slot region, and outer radiation belt. Power law spectral gradients in the outer belt are typically −2.5 during quiet periods, changing to a softer spectrum of ∼−3.5 during geomagnetic storms. The inner belt does the opposite, hardening from −4 during quiet times to ∼−3 during storms. Typical outer belt e‐folding values are ∼200 keV, dropping to ∼150 keV during geomagnetic storms, while the inner belt e‐folding values change from ∼120 keV to >200 keV. Analysis of geomagnetic storm periods show that the precipitating flux enhancements evident from such storms take approximately 13 days to return to normal values for the outer belt and slot region and approximately 10 days for the inner belt.